Then and now: The progress in hepatitis B treatment over the past 20 years - Halegoua-De Marzio, Dina (Baishideng Publishing Group Co., Limited, 2014)
The ultimate goals of treating chronic hepatitis B (CHB) is prevention of hepatocellular carcinoma (HCC) and hepatic decompensation. Since the advent of effective antiviral drugs that appeared during the past two decades, considerable advances have been made not only in controlling hepatitis B virus (HBV) infection, but also in preventing and reducing the incidence of liver cirrhosis and HCC. Furthermore, several recent studies have suggested the possibility of reducing the incidence of recurrent or new HCC in patients even after they have developed HCC. Currently, six medications are available for HBV treatment including, interferon and five nucleoside/nucleotide analogues. In this review, we will examine the antiviral drugs and the progresses that have been made with antiviral treatments in the field of CHB.